Assessment of the Effectiveness and Security of Emergency Abdominal Wall Hernia Prosthetic Mesh Repair - NK Khiro; MA Hamdawi; BA Abdulhassan (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: The method of repair in complicated ventral hernia at emergency setting imposes a great challenge to the surgeon worldwide. Using polypropylene mesh is very challenging because of the great concern about risks of complications. This study was conducted to determine the safety and efficiency of polyproline mesh in complicated emergency ventral hernia. Methods: This prospective study was conducted on 60 patients with complicated abdominal hernia who required emergency surgery (obstructed and or strangulated). The cases were divided based on the type of repair into two groups: prosthetic mesh repair and suture repair. Patients were followed up for a median of 14.2 months after operation during which surgical infection, seroma formation and recurrence rate were evaluated in both groups. Findings: The common type of hernia encountered in this research was paraumbilical hernia compromising 80% (48 patients) of the total patients followed by recurrent paraumbilical hernia (11.66%). Superficial surgical infection and seroma developed in 15.38% (4 patients) in the mesh group and in 8.82% (3 patients) in the suture repair group with no significant differences. The recurrence rate was 8 people (23.52%) in the suture group and 2 people (7.69%) in the mesh group; however, this difference was not significant. Conclusion: The results showed that the use of prosthetic mesh in the repair of emergent complicated ventral abdominal wall hernia is feasible choice with low risk of complications.